Strategi Dinas Perpustakaan dan Kearsipan Aceh Tengah dalam Pengelolaan Perpustakaan Berbasis Digital - Vivi Mauliza; Retno Sayekti; Yusniah Yusniah (Politeknik Kampar, 2024)
Digital-based libraries play a role in disseminating information to all levels of society, taking into account the information needs of digital society. The aim of this research is to determine the strategy of the Central Aceh Library and Archives Service in Digital-Based Library Management regarding provision, provision of facilities and infrastructure, and human resources. This research uses qualitative research methods with a descriptive approach. The data collection techniques used were interviews and observation. The findings in this research are that the Central Aceh library and archives service has not yet fulfilled a digital library management strategy that covers the entire general public. Where their funds are still very minimal to manage digital libraries. Facilities and infrastructure that are still inadequate mean that the library cannot keep up with the rapid development of the times. And inadequate human resources make the progress of digital libraries a bit time-consuming.